Predictors of Women’s awareness of common non-communicable diseases screening during preconception period in Manna District, Southwest Ethiopia: implication for wellness check-up - Gonfa, Firanbon Teshome (BMC Health Serv Res, 2021)
BACKGROUND: Non-communicable diseases (NCDs) are the dominant cause of global morbidity and mortality, especially in developing countries. Tackling NCDs is central to advancing women’s and child health, and future generations. Many NCDs can be prevented with appropriate approaches across the maternal and child health life-cycle, throughout the years of reproductive age especially before conception and continuing through pregnancy. However, women’s awareness of NCDs screening during the preconception period was not well known in many countries including Ethiopia. Therefore, this study aimed to assess women’s awareness of common NCDs screening during the preconception period and associated factors in Manna District, Jimma Zone, Oromia Region, Ethiopia, 2019. METHODS: A community-based cross-sectional study was conducted from March 02 to April 10, 2019. The sample size was 636 pregnant women from eight randomly selected rural kebeles and a purposively taken urban kebele. The data were collected using a pre-tested structured questionnaire and entered into Epi data manager version 4.0.2 and exported to SPSS version 21. Descriptive, binary, and multivariable logistic regression analyses were carried out. RESULTS: Of the total of 623 respondents, 459 (73.7%) of them had good awareness of common NCDs screening during the preconception period. Women who had formal education [AOR = 1.95, 95% CI: (1.31–2.89)], those who had planned pregnancy [AOR = 2.17, 95% CI: (1.47–3.19)], on ANC follow up [AOR = 1.79, 95% CI: (1.16–2.74], and those who had media (radio and/or television) in their house [AOR = 1.55, 95% CI: (1.05–2.29)] had good awareness on common NCDs screening during the preconception period compared to their counterparts. CONCLUSIONS: In this study, nearly three-quarters of respondents had a good awareness of common NCDs screening during the preconception period. Women’s educational status, pregnancy planning status, ANC visit, and having radio and/or television in the house were predictors of women’s good awareness of common NCDs screening during the preconception period. Therefore, all concerned bodies are recommended to work toward increasing women’s awareness using different approaches like awareness creation campaigns and counseling clients attending health facilities.